Neoliberalism, COVID, anti-science, and the politics of school reopening - Kretchmar, Kerry; Brewer, T. Jameson (Education Policy Analysis Archives, 2022)
This paper explores the politicization of school reopenings in two swing states against the backdrop of rising COVID cases, public health warnings, and the hyper-partisan weaponization of “choice” rhetoric by parents to send children back into school. Rhetoric surrounding parental choice partnered with economic considerations placed significant pressure on school boards to navigate their reopening plans from a partisan frame of reference. We explore, compare, and contrast the landscape of school reopening plans in Wisconsin and Georgia, which both served as pivotal states in the contentious 2020 Presidential election. Within each state we consider two districts that are situated in either a more traditionally conservative or liberal environment. Our guiding questions are: (1) How is the conversation about school reopening reflective of politicized and polarized approaches to COVID? and, (2) How are school reopening discussions different in politically liberal and conservative communities?